Lean Principles Improving Entrepreneurial Ecosystem in Malaysian SMEs - Azyyati Anuar; Daing Maruak Sadek; Nurul Labanihuda Abdull Rahman; Norasmah Othman (International Journal of Supply Chain Management, 2020)
Lean business ideology has been one of the ongoing prevailing research areas in operations management. Accomplishment of lean can be found in manufacturing, construction, textile, service and other industrial areas. Still, the interest revealed in lean by small and medium enterprises (SMEs) is limited. SMEs is one of the most indispensable substances that contribute extensively in building up Malaysia's economy. Albeit the SMEs is currently important towards Malaysia’s economy, however does the SMEs offer a superior entrepreneurial ecosystem. Therefore, the point of this research is to explore how lean principles can improve the entrepreneurial ecosystem in Malaysian SMEs. This research will be directed subjectively by utilizing triangulation of subjective information sources containing document analysis, interview and archival record. The validity of the findings will utilize the elements of trustworthiness to ensure the data precise and dependable. The expected findings of this study may demonstrate lean principles will improve the entrepreneurial ecosystem in SMEs Malaysia. In addition, it is urged to improve or cultivate the entrepreneurial ecosystem in accordance with the National Entrepreneurial Policy (NEP) 2030 by taking a gander at the Industrial Revolution 4.0, the digital economy and the intellectual economy to create high worth ventures, in this way staying significant and satisfying future financial needs.